Process standardization of dried nile tilapia (Oreochromi sniloticus). - Ines, Ma Clarissa (College of Fisheries and Ocean sciences, University of the Philippines, 2013)
Dried tilapia samples were prepared using different salt concentration (5%, 9% and 15%) and with different soaking times (30min, 2 hour and 1hour and 30 minutes). Using the analysis of variance (ANOVA), effects of different salt concentration soaking time on the samples were analyzed correlations between the physiological indicators (Proximate analysis and moisture content) and sensory qualities (appearance color. Flavor, texture, odor and general acceptability) were also conducted. Soaking solutions with different concentrations (5%,1 Hr and 15% Mins.) used in tilapia, (o. niloticus) at different soaking times (30 mins, 1 hour and 1 hour and 30 mins.) were found to prevent microbial growth and to improve the sensorial characteristics of the product. In general. Lower % moisture content was obtained on samples with higher salt concentration with different soaking time particularly in longer soaking period. Soaking time of 30mins, 1 hr and 1 and 30 minutes did not significantly affect (P<0.05) the sensorial quality of the product, including its appearance (color), texture, flavor and odor. With % moisture content determined and sensory evaluation conducted the results showed that 15% of salt concentration with 30 mins soaking time gave the product the desired quality. Sensory analysis showed higher score acceptability on samples treated with higher salt concentration (15% salt concentration). Overall, there were significant differences between the samples soaked in solution with different salt concentration and at different soaking times.